Al-Qasas al-Nabawi dalam karya Abū Isḥāq al-Huwaynī dan ‘Umar Sulaymān al-Ashqar: kajian perbandingan = Al-Qasas al-Nabawi in the works of Ab Isq al-Ḥuwayn and Umar Sulaymn al-Ashqar: A comparative study) - Muhammad Arif Yahya, Muhammad Arif Yahya; Khairulnazrin Nasir, Khairulnazrin Nasir; Muhammad Ikram Abu Hassan, Muhammad Ikram Abu Hassan (USIM Press (Penerbit USIM), 2021)
The hadiths ofRasulullah SAW have various contents, including the stories narrated by the Prophet SAW. These hadiths are known as al-Qasas al-Nabawi. The approach to conveying the story is one of the uniqueness of the Prophet SAW in conveying knowledge and education. This study aims to examine the method of writing the works of al-Qasas al-Nabawi, which are compiled by modern writers and not presented thematically in major hadith works such as Kutub al-Sittah or Kutub al-Tisah. Abu Ishaq al-Huwaini and Umar Sulayman al-Asyqar are among the modern writers who have compiled these hadiths relating to al-Qasas al-Nabawi in their works. However, there are differences in the method of compilation and presentation of this hadith by the two authors, although authentic hadith were used as the basis of the study. The methodology of this study uses a qualitative study design with the method of content analysis on the work of al-Qasas al-Nabawi by Abu Ishaq al-Huwaini and Umar Sulayman al-Asyqar. The results of the study found that these two scriptures use the same method in selecting only the authentic hadith related to al-Qasas al-Nabawi, but have different methods in other aspects. The different methods used by the two authors include the choice of topics included in the hadith, the number of hadiths discussed, and the approach to presenting the teachings at the end of each hadith. In addition, the work of al-Qasas al-Nabawi by Abu Ishaq al-Huwaini is more concise and not suitable as a reference work for the public, as the author notes in the foreword to this book. The work of al-Qasas al-Nabawi by Umar Sulayman al-Asyqar is more systematic and useful as a guide for the public to understand the authentic hadith in the category of al-Qasas al-Nabawi. Keywords: Works by al-Qasas al -Nabawi, Abu Ishaq al-Huwaini, Umar Sulayman al-Asyqar, Authentic Hadith.